Metabolite Profiling the Cerebral Spinal Fluid in Subarachnoid Hemorrhage: Insights into Patient Outcomes. (1st September 2019) - Koch, Matthew J; Ament, Zsuzsanna; Hansen, Christina; Bevers, Matthew; Stapleton, Christopher J; Patel, Aman B; Kimberly, W Taylor
Abstract: INTRODUCTION: Aneurysmal subarachnoid hemorrhage (aSAH) continues to have poor neurologic outcomes. Prior studies demonstrate elevations of CSF metabolites, specifically the structurally similar but functionally different Asymmetric and Symmetric Dimethyl Arginine (ADMA, SDMA) may correlate with vasospasm and patient outcome in smaller cohorts of patients. We performed CSF metabolite profiling of subarachnoid hemorrhage to corroborate these findings and further understand the disease. METHODS: CSF of 74 aSAH patients were enrolled in a biorepository study between 2011 and 2018 and CSF from 16 electively clipped aneurysms (90 patients total), underwent metabolite profiling. CSF samples were collected at 3 time epochs (early: days 0-5 after aSAH, peak vasospasm: days 6-10, late: days 11-15). Delayed cerebral ischemia, vasospasm, Discharge and 90-d outcome were assessed retrospectively and with patient followup phone calls. CSF samples were analyzed using liquid chromatography-tandem mass spectrometry (LC-MS/MS). A total of 155 metabolites were initially measured and quantified in each sample. Metabolites were tested for association with DCI, vasospasm and outcome using logistic regression and ANOVA performed in R. RESULTS: Screening of CSF metabolite levels at 3 time epochs identified 13 candidate metabolites that were correlated with discharge mRS, and mRS at 90 d. Only (SDMA) demonstrated significantly different levels when compared to control cerebral spinal fluid, ( P  = .009), ADMA was not significantly different, ( P  = .183). Statistical analysis yielded significant correlation of SDMA concentrations at the "early" time epoch with poor mRS at 90 d on univariate and multivariate analysis ( P  = .001 and P  = .03, respectively), with an odds ratio of 6.5 (95% CI 1.17-36.7). No significant association with vasospasm or DCI was observed. CONCLUSION: SDMA, not ADMA, is associated with poor outcome after aSAH in our cohort. Further study of the role of SDMA in aSAH and its potential utility as a biomarker is warranted to better understand and treat this pathology.